2008
DOI: 10.1103/physreve.77.061116
|View full text |Cite
|
Sign up to set email alerts
|

Multicritical points for spin-glass models on hierarchical lattices

Abstract: The locations of multicritical points on many hierarchical lattices are numerically investigated by the renormalization group analysis. The results are compared with an analytical conjecture derived by using the duality, the gauge symmetry and the replica method. We find that the conjecture does not give the exact answer but leads to locations slightly away from the numerically reliable data. We propose an improved conjecture to give more precise predictions of the multicritical points than the conventional on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(81 citation statements)
references
References 25 publications
6
75
0
Order By: Relevance
“…Since the series of work [3][4][5][6] revealed that the duality is capable to estimate the approximate values of the critical points even for such complicated systems, the duality has been developed as one of the rare successful approaches to finite-dimensional spin glasses, where very little analytical work exists. More precise analysis of the locations of the critical points in spin glasses has been performed by employing a real-space renormalization technique, i.e., the partial summation of the degree of freedom [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Since the series of work [3][4][5][6] revealed that the duality is capable to estimate the approximate values of the critical points even for such complicated systems, the duality has been developed as one of the rare successful approaches to finite-dimensional spin glasses, where very little analytical work exists. More precise analysis of the locations of the critical points in spin glasses has been performed by employing a real-space renormalization technique, i.e., the partial summation of the degree of freedom [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Similar previous studies, on other spin-glass systems, are reported in Refs. [12,13,[40][41][42][43][44][45][46][47]. Figure 1 shows a calculated sequence of phase diagram cross sections for the left-chiral (c = 0) (top row) and quenched random left-and right-chiral (c = 0.5) (bottom row) systems with, in both cases, quenched random ferromagnetic and antiferromagnetic interactions.…”
Section: Renormalization-group Method: Migdal-kadanoff Approximamentioning
confidence: 99%
“…To account for this, a renormalisation inspired expansion was introduced in [11,20] to account for corrections. While most natural for hierarchical lattices [20], it has been extended to square lattices and achieves an even tighter match with previous numerical results using only a first order correction [11]. This technique proceeds by replacing the term e J H in x H 0 (and, similarly, the term e J H + e −J H in x * H 0 ) with an equivalent effective weight arising from an averaging effect over several neighbouring spins.…”
Section: B Replica Methodsmentioning
confidence: 99%